2011
DOI: 10.1121/1.3518770
|View full text |Cite
|
Sign up to set email alerts
|

Long-time trends in ship traffic noise for four sites off the North American West Coast

Abstract: Measurements (1994-2007) from four cabled-to-shore hydrophone systems located off the North American west coast permit extensive comparisons between "contemporary" low frequency ship traffic noise (25-50 Hz) collected in the past decade to measurements made over 1963-1965 with the same in-water equipment at the same sites. An increase of roughly 10 dB over the band 25-40 Hz at one site has already been reported [Andrew et al., Acoust. Res. Lett. Online 3(2), 65-70 (2002)]. Newly corrected data from the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 8 publications
6
68
1
1
Order By: Relevance
“…Prior to this event, long-term noise levels in the Pacific (EEP-NW) and the regional iceberg volume were both increasing, but the trends are too subtle to determine a robust relationship between the two time series. It is not clear if the iceberg volume in the Pacific-Antarctic region would have contributed to the noise leveling or decreasing as recently observed in the midlatitude of North American West Coast [Andrew et al, 2011], where shipping and local seasonal winds are considered to be the dominant low-frequency noise sources. The distance from 60 S to the North American West Coast hydrophones is only 15 % larger than the distance to the EEP-NW.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Prior to this event, long-term noise levels in the Pacific (EEP-NW) and the regional iceberg volume were both increasing, but the trends are too subtle to determine a robust relationship between the two time series. It is not clear if the iceberg volume in the Pacific-Antarctic region would have contributed to the noise leveling or decreasing as recently observed in the midlatitude of North American West Coast [Andrew et al, 2011], where shipping and local seasonal winds are considered to be the dominant low-frequency noise sources. The distance from 60 S to the North American West Coast hydrophones is only 15 % larger than the distance to the EEP-NW.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, along the North American West Coast, Andrew et al [2011] show the same low-frequency noise seasonality with a few decibel of dynamic range and a wideband spectrum consistent with the characteristics of ice-generated noise observed at high southern latitudes [e.g., Dziak et al, 2013].…”
Section: Iceberg Volume Versus Acoustic Noise Levels In the Pacificmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, passive acoustic recordings of these lower-frequency fish bands may provide a better evaluation of community assemblages. Ocean noise levels are increasing at low frequencies as a result of commercial shipping activities (Andrew et al, 2011;McDonald et al, 2006;Chapman and Price, 2011). While most of these increases are below 300 Hz, an elevated low-frequency noise floor could have adverse effects on acoustic communication in fishes and, by extension, larval recruitment to reefs.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings from the north Pacific Ocean indicated that low-frequency ambient noise levels increased by approximately 3 dB per decade from , potentially as a result of commercial shipping activity (McDonald et al, 2006). More recent estimates have suggested lower but positive rates of increase in that location (Andrew et al, 2011). Similarly, in the Atlantic Ocean, recordings taken near Bermuda have suggested low but positive rates of increase in ambient low-frequency ocean noise over time (Sirović et al, 2016).…”
Section: Anthropogenic Noisementioning
confidence: 99%